Enhancement of Solar Still Production - Ismail, Al Emran; Faizon, Wan Mohammad Ezudin (Research Progress in Mechanical and Manufacturing Engineering, 2021)
In this recent years, the issues about an environment pollution and increasing population is main concerns. The potable or clean water is reducing and being contaminated on a daily basis. Thus, there is some research focused on get a potable water by using a desalination process from a saltwater. Solar still technology is one of the best methods on solving the issues because it using free solar energy. The computational fluid dynamic CFD model of solar still is one of the best method on study the improvement of the conventional solar still because it reduces the need of conducting an experiments. The main purpose of this study is to design a solar still that well function and determine the best design of solar still to be function in Malaysia climate. In this study, the performance of the solar still is investigated by using different angle of slope and predicts the performance without any experiment measure, depends on the CFD solar radiation model. In the parameter that have been investigated, the best angle of slope of double slope in Malaysia climate was based on the temperature difference between the glass and the collector. In this study, the results that was generate from the ANSYS Workbench 2020 in climate conditions of Kuala Lumpur, Malaysia (latitude 4.2105° N and longitude 101.9758° E). The results indicated that the 20 degrees angle of slope of double slope solar still were found to be the admirable design to be used in Malaysia climate at water depth of 2cm.